Ferroelectric memory: state-of-the-art manufacturing and research - D. A. Abdullaev; R. A. Milovanov; R. L. Volkov; N. I. Borgardt; A. N. Lantsev; K. A. Vorotilov; A. S. Sigov (Российский технологический журнал)
Semiconductor industry calls for emerging memory, demonstrating high speed (like SRAM or DRAM), nonvolatility (like Flash NAND), high endurance and density, good scalability, reduced energy consumption and reasonable cost. Ferroelectric memory FRAM has been considered as one of the emerging memory technologies for over 20 years. FRAM uses polarization switching that provides low power consumption, nonvolatility, high speed and endurance, robust data retention, and resistance to data corruption via electric, magnetic fields and radiation. Despite the advantages, market share held by FRAM manufacturers is insignificant due to scaling challenges. State-of-the-art FRAM manufacturing is studied in this paper. Ferroelectric capacitors and memory cells made by main commercial FRAM manufactures (Texas Instruments, Cypress Semiconductor, Fujitsu и Lapis Semiconductor) are explored. All memory cells are based on the lead zirconate titanate PZT capacitor with the thickness of about 70 nm and IrOx/Ir or Pt electrodes. The leading FRAM technology remains the 130 nm node CMOS process developed at Texas Instruments fabs. New approaches to further scaling and new devices based on ferroelectrics are reviewed, including binary ferroelectrics deposited by ALD techniques, piezoelectronic transistors, ferroelectric/2D-semiconductor transistor structures, and others. Whether FRAM technology will be able to resolve one of the main contradictions between a high-speed processor and a relatively slow nonvolatile memory depends on the success of the new technologies integration.